Confusion in the Study of Immune Reconstitution Inflammatory Syndrome - Claudia Alvarado-de la Barrera; Gustavo Reyes-Terán (Case Western Reserve University, 2017)
As a consequence of late presentation for HIV care, a significant proportion of individuals develop immune reconstitution inflammatory syndrome (IRIS) soon after initiation of antiretroviral therapy. Incidence, predictors, and models of pathogenesis of IRIS vary in the literature. Here we discuss factors that may contribute to this lack of consensus. We propose that different pathogens drive different types of IRIS and suggest that these clinical conditions should be studied individually and not grouped under the general heading of "IRIS."